On mechanism of intermediate-sized circular DNA compaction mediated by spermine: contribution of fluorescence lifetime correlation spectroscopy - Humpolícková, Jana; Stepánek, Miroslav; Kral, Teresa; Benda, Ales; Procházka, Karel; Hof, Martin (Journal of fluorescence, 2008)
The compaction of DNA plays a role in the nuclei of several types of cells and becomes important in the non-viral gene therapy. Thus, it is in the scope of research interest. It was shown, that spermine-induced compaction of large DNA molecules occurs in a discrete "all-or-non" regime, where the coexistence of free and folded DNA molecules was observed. In the case of intermediate-sized DNA molecules (approximately 10 kbp), so far, it was stated that the mechanism of folding is continuous. Here, we show, that neither a standard benchmark technique-dynamic light scattering, nor a single molecule technique such as fluorescence correlation spectroscopy, can decide what kind of mechanism is undertaken in the compaction process. Besides, we introduce an application of a new approach-fluorescence lifetime correlation spectroscopy. The method takes an advantage of a subtle lifetime change of an intercalating dye PicoGreen during the titration with spermine and based on that, it reveals the discrete mechanism of the process. Furthermore, we show that it allows for observation of the equilibrium state transition dynamics.
Keywords: konformace nukleové kyseliny; algoritmy; Models, Molecular; Nucleic Acid Conformation; fluorescenční spektrometrie; Algorithms; Light; světlo; Organic Chemicals; Spectrometry, Fluorescence; Scattering, Radiation; radiační rozptyl; spermin; molekulární modely; DNA, Circular; Plasmids; Spermine; plazmidy; organické látky; kruhová DNA